Proposed proactive digital forensic approach for cloud computing environment - Samy G.N.; Maarop N.; Wong D.H.; Rahim F.A.; Hassan N.H.; Magalingam P.; Albakri S.H.; Sundresan Perumal (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA